Feasibility study of microburst VNS therapy in drug-resistant focal and generalized epilepsy - Cornelia Drees; Pegah Afra; Ryan Verner; Lesley Kaye; Amy Keith; Mei Jiang; Jerzy P. Szaflarski; Kathryn Nichol; Danielle McDermott; Mesha Gay Brown; Michael Macken; Irena Bellinski; et al. (Brain Stimulation, 2024)
Background: Vagus nerve stimulation (VNS) at low frequencies (≤30 Hz) has been an established treatment for drug-resistant epilepsy (DRE) for over 25 years. Objective: To examine the initial safety and efficacy performance of an investigational, high-frequency (≥250 Hz) VNS paradigm herein called “Microburst VNS” (μVNS). μVNS consists of short, high-frequency bursts of electrical pulses believed to preferentially modulate certain brain regions. Methods: Thirty-three (33) participants were enrolled into an exploratory feasibility study, 21 with focal-onset seizures and 12 with generalized-onset seizures. Participants were titrated to a personalized target dose of μVNS using an investigational fMRI protocol. Participants were then followed for up to 12 months, with visits every 3 months, and monitored for side-effects at all time points. This study was registered as NCT03446664 on February 27th, 2018. Results: The device was well-tolerated. Reported adverse events were consistent with typical low frequency VNS outcomes and tended to diminish in severity over time, including dysphonia, cough, dyspnea, and implant site pain. After 12 months of μVNS, the mean seizure frequency reduction for all seizures was 61.3% (median reduction: 70.4%; 90% CI of median: 48.9%–83.3%). The 12-month responder rate (≥50% reduction) was 63.3% (90% CI: 46.7%–77.9%) and the super-responder rate (≥80% reduction) was 40% (90% CI: 25.0%–56.6%). Participants with focal-onset seizures appeared to benefit similarly to participants with generalized-onset seizures (mean reduction in seizures at 12 months: 62.6% focal [n = 19], versus 59.0% generalized [n = 11]). Conclusion: Overall, μVNS appears to be safe and potentially a promising therapeutic alternative to traditional VNS. It merits further investigation in randomized controlled trials which will help determine the impact of investigational variables and which patients are most suitable for this novel therapy.